Dakwah Melalui Film: Sebuah Kajian Aksiologi - Arina Rahmatika (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2021)
The rapid development of information and communication tools makes da'wah must be transformed according to the times, one of which is through film media. Da'wah through films can be seen from how the internalization of Islamic values in the film. In addition, film as a medium of mass communication has the opportunity to be a means to guide Muslims through the Islamic values contained in the film. The merging of da'wah and film as an expression of art and culture produces contemporary da'wah, alternative da'wah and transformative da'wah. However, to find out the extent to which the nature and benefits and values of Islam are contained in the film, it is necessary to discuss the da'wah film from various axiological perspectives, both in terms of use values, ethical values, aesthetic values and Islamic values.Keywords: Da’wah, Film, Axciology